Organizational resilience and transformational leadership for managing complex school systems - Zadok, Ayala; Benoliel, Pascale; Schechter, Chen (Frontiers in Education, 2024)
Introduction In the context of global challenges facing educational institutions, this study explores the dynamics between transformational leadership, collective teacher efficacy, and organizational resilience in school systems. Specifically, it examines the mediating role of collective teacher efficacy in the relationship between middle leaders’ transformational leadership and organizational resilience. Methods The study involved data collection from 103 middle-leaders and 506 randomly selected secondary school teachers across Israel. Structural equation modeling was used to analyze the data, focusing on the mediating role of collective teacher efficacy in the relationship between transformational leadership and organizational resilience. Results The analysis revealed that collective teacher efficacy fully mediates the relationship between middle-leaders’ transformational leadership and organizational resilience. Middle-leaders’ transformational leadership positively impacts collective teacher efficacy, which in turn enhances organizational resilience. The study’s findings suggest that educational institutions can significantly increase their organizational resilience by fostering transformational leadership and strengthening collective teacher efficacy. Discussion The implications of these findings are both theoretical and practical. Theoretically, the study expands the understanding of the interplay between leadership styles and organizational resilience in educational settings. Practically, it provides insights for educational policymakers and practitioners aiming to enhance the resilience of schools by promoting transformational leadership and collective teacher efficacy.